Spatial and temporal variation of dung beetle assemblages in a fragmented landscape at eastern humid Chaco - Damborsky, Miryam Pieri (2014)
Fil: Damborsky, Miryam Pieri. Universidad Nacional del Nordeste. Facultad de Ciencias Exactas y Naturales y Agrimensura; Argentina.